Penerapan Komponen Bahasa pada Framework ELPSA untuk Meningkatkan Pemahaman Konsep Matematika Siswa Kelas VII pada Materi Melukis Sudut - Yunita, Yunita (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
Language is an important point in interacting, especially in the learning process and one of the tools to facilitate student understanding. In the learning process there are often misconceptions between teachers and students, this happens because of the lack of emphasis on language during learning, therefore this study aims to improve students' understanding of mathematical concepts through the Language or L component of the ELPSA framework. This study is a classroom action research. This research was conducted in a class involving 30 MTsN 2 Mataram students. The research instruments used are observation sheets and test sheets. The results showed that students were very enthusiastic in learning to paint with the specified Step Step. Through the application of language components in the ELPSA framework, it can improve the understanding of mathematical concepts of Grade VII students in Corner Painting Material